LIVING ROOM VENTILATION AND URBAN ENVIRONMENTAL HEALTH CASE IN DKI JAKARTA - Frimawaty, Evi; Kamiluddin, Muhammad Mundzir (Journal of Environmental Science and Sustainable Development, 2020)
In developing countries, on average, one out of five children die from pneumonia. Death from pneumonia is most prevalent in Southeast Asia, particularly in Indonesia. Many factors can cause pneumonia. In Jakarta, the prevalence period of pneumonia in toddlers reached 19.6‰, which is higher than the national prevalence period of only 18.5‰. This study used a cross-sectional research design to analyze the relationship between disease prevalence and risk factors simultaneously. Results showed that, out of 721 children under 5 years old investigated in this study, 31 toddlers suffered from pneumonia. Furthermore, bivariate analysis showed that two variables were related to the incidence of pneumonia, namely, low maternal education (odds ratio [OR] = 2.325, 95% confidence interval [CI] = 1.093–4.946) and living room ventilation10% of the total space because the lack of air circulation induces the transmission of pneumonia.